Effects of hydrological regime on Taxodium ascendens plant decomposition and nutrient dynamics in the Three Gorges Reservoir riparian zone - Chen, Zhangting; Song, Hong; Arif, Muhammad; Li, Changxiao (Frontiers in Environmental Science, 2022)
Riparian plants are an integral part of the river ecosystem and have significant impacts on the water quality of the reservoir area. The special hydrological process of the riparian zone makes it possible to become a "source" or "sink" of organic matter and nutrients. This study quantifies the flooding period on the decomposition as well as nutrient dynamics of leaves from artificially regenerated Taxodium ascendens in the riparian zone of the Three Gorges Reservoir (TGR) in China. Five decomposition treatment groups were exposed to 10, 30, 60, 90, and 180 days of decomposition: conventional water (T1), mild drought stress (T2), saturated water content (T3), light flooding stress (T4), and severe flooding stress (T5). In T4 and T5, the decomposition rate of T. ascendens leaves was significantly higher than that of T1, T2, and T3. All the leaf C, N, P, and K concentrations at the end of the test were lower than their respective starting values. The concentrations of N and P in the overlying water decrease to various degrees due to decomposition. At the end of the study, the TN content was 1.34 times (T4) and 1.16 times (T5) higher than that of the control group, and the TP content was 3.97 times (T4) and 3.21 times (T5) higher than that of the control group. Leaf decomposition increases the content of N and P in the overlying water under flood conditions, which adversely affects the water environment. This study establishes a theoretical framework for understanding how hydrological processes affect leaf decomposition and nutrient release in riparian areas, providing a scientific basis for riparian zone management in TGR.